‘I want to create my own space’. A time-geographic analysis of the lives of children and young people on the streets of Pelotas, Brazil - Gadd, Katri (fi=Turun yliopisto|en=University of Turku|, 2016)
Children and young people who drift about the streets working, having fun, relaxing in the shade or committing petty crimes are an increasingly visible part of the dynamics in cities around the world. They are often misunderstood, despite researchers’ aspirations to diminish the gap between the common understanding about street realities and the realities experienced by the children and young people in street situation. Researchers attempt to demonstrate this reality by covering the varied aspects of street life such as; street life style, the reasons for migrating to the streets, survival strategies, identity, and agency. Owing to the misconceptions, the activities of these children and young people are frequently misinterpreted by societies in general, and the children and young people are represented as the primary causes of the accretion in social evils, such as crime, drugs, or prostitution. However, the elements of street life are highly inextricable and should be kept together in analyses of street realities. These inextricable elements include, mentioning but a few, mental and social elements and their interrelations with the physical street environments and vice versa. Moreover, within the social sciences, little focus has been given to aspects such as sadness, depression, low self‐esteem, and other mental burdens create by living on the streets. All these aspects, whether human or non‐human have different meanings for individuals; aspects are interpreted in a variety of ways and affecting how livelihoods are experienced. In this thesis, I explore the lives of children and young people living on the streets of Pelotas in southern Brazil using a time‐geographic methodology, which provides a useful perspective in order to investigate children’s and adolescents’ lives on the streets. I have three concrete research questions in this dissertation: 1. What processes impact the multidimensional networks within which children and young people on the streets are connected? 2. How are the relationships of these children and young people with their street environments formed in relation to space and time? 3. What are the processes behind the actions of children and young people on the streets? I investigated 19 children and young people, and their relationships with their multidimensional environment using various traditional methods such as observation, interviews, and focus group discussions. I also used self‐designed exercises and walkabouts and analysed poems, lyrics, and photographs taken by the participants. My interest was primarily on the interconnections between different elements from the mental, socio‐cultural dimensions of space, and the physical street environments where my participants were visibly present. Furthermore, I illustrate how they actively structure their lives on the streets. This dissertation illustrates the how the highly relational nature of street life is shaped by the constantly changing succession of encounters and dispersions of the manifold elements that form the complex networks of the streets. These networks are shaped by multiple intertwined processes, which connect different times and spaces. The legacy of past times, in the form of outdated legislation, repute, or the ways in which street living people are portrayed in the media or even in fiction, impact the networks of children and youths who are living on the streets. Moreover, children and young people actively transform the networks within which they are connected. To a great extent, these same processes, which shape the networks of street children, are behind the activities of the children and young people, i.e. certain elements in the environment are approached physically or in the imagination in order to reach one’s own goals. The goals are often related to possibilities to create a better means of survival and live as normal a life as possible, in one way or another. To reach their goals these children and young people create space‐time pockets either physically, by socially forming them, or merely imagining. The relationships children and young people on the streets develop with the environment are the result of constant negotiation between one’s own desires and wants in relation to what is perceived as affordable in the environment for the person. This complex negotiation is also affected by past experiences, as well as by hopes for the future.

Lapset ja nuoret, jotka kuljeskelevat kaduilla työskennellen, pitäen hauskaa, rentoutuen viileissä varjoissa tai pikku rikoksia tehden, ovat enenevässä määrin näkyvä osa kaupunkien dynamiikkaa ympäri maailman. He ovat usein väärinymmärrettyjä, huolimatta tutkijoiden yrityksistä pienentää yleisen käsityksen ja koetun katutodellisuuden välistä kuilua tutkimalla useita katuelämän aspekteja, kuten katuelämäntapoja, kadulle muuton syitä, selviytymiskeinoja, katulasten identiteettiä ja toimijuutta. Väärinymmärrysten takia yhteiskunta tulkitsee tämän tästä väärin kadulla elävien lasten ja nuorten toimintaa ja heidät nähdään usein sosiaalisten epäkohtien, kuten rikollisuuden, huumeiden ja prostituution, ensisijaisina syinä. Elementtejä, joista katuelämä muodostuu, ei voida kuitenkaan erottaa toisistaan, vaan ne tulisi pitää yhdessä katutodellisuutta analysoitaessa. Tällaisia elementtejä ovat muun muassa henkiset ja sosiaaliset elementit sekä niiden yhteydet fyysiseen kaupunkitilaan ja päinvastoin vain muutaman mainitakseni. Yhteiskuntatieteissä ei ole myöskään riittävästi huomioitu aspektien, kuten surun, ahdistuksen ja huonon itsetunnon tai muiden henkisesti kuormittavien tekijöiden, vaikutusta kadulla. Kaikilla näillä aspekteilla, inhimillisillä tai ei‐inhimillisillä, on erilainen merkitys eri yksilöille; aspektit tulkitaan eri tavoin, joka vaikuttaa siihen, miten elinolot koetaan. Tässä väitöskirjassa tutkin kadulla elävien lasten ja nuorten elämää Pelotaksessa Etelä‐Brasiliassa käyttäen aika‐maantieteellistä metodologiaa, joka tarjoaa hyödyllisen näkökulman kadulla elävien lasten ja nuorten elämien tutkimiseen. Väitöskirjassani minulla on kolme konkreettista tutkimuskysymystä: 1. Mitkä prosessit vaikuttavat moniulotteisiin verkostoihin, joihin kaduilla elävät lapset ja nuoret ovat kytkeytyneet? 2. Miten kyseisten lasten ja nuorten suhde katuympäristöön muodostuu suhteessa tilaan ja aikaan? 3. Mitkä prosessit ovat kadulla elävien lasten ja nuorten toimien taustalla? Tutkin 19 lasta ja nuorta ja heidän suhteitaan moniulotteiseen ympäristöön hyödyntäen monia perinteisiä metodeja, kuten havainnointia, haastattelua sekä ryhmäkeskusteluja. Käytin myös itse suunnittelemiani harjoituksia, kuten kävelykierroksia, ja analysoin lasten kirjoittamia runoja, ja sanoituksia sekä valokuvia, joita he ottivat. Olen erityisesti kiinnostunut henkisten, sosio‐kulttuuristen tilan ulottuvuuksien sekä fyysisen katuympäristön välisistä yhteyksistä. Tämän lisäksi havainnollistan miten kadulla elävät lapset ja nuoret aktiivisesti itse muokkaavat elämiään kadulla. Tämä väitöskirja osoittaa katuelämän riippuvan monesta tekijästä ja muokkaan‐tuvan jatkuvasti muuttuvien kohtaamisten ja erkanemisten vaikutuksesta monimutkaisiksi verkostoiksi. Monet yhteenkietoutuneet prosessit muokkaavat näitä verkostoja yhdistäen eri aikoja ja tiloja. Menneisyyden perintö, kuten vanhentunut lainsäädäntö, maine tai se miten katulapset kuvataan mediassa tai fiktiossa, vaikuttavat kadulla elävien lasten ja nuorten verkostoihin. Tämän lisäksi lapset ja nuoret muovaavat itse verkostoja, joihin he ovat liitoksissa. Suuressa määrin samat prosessit ovat näiden lasten ja nuorten toiminnan taustalla; määrättyjä ympäristön elementtejä lähestytään fyysisesti tai mielikuvituksessa, jotta omien tavoitteiden saavuttaminen olisi mahdollista. Tavoitteet liittyvät usein tavalla tai toisella selviytymismahdollisuuksien kehittämiseen ja mahdollisuuteen elää niin normaalia elämää kuin mahdollista. Saavuttaakseen tavoitteensa kadulla elävät lapset ja nuoret muodostavat aika‐tilataskuja joko fyysisesti, sosiaalisesti tai kuvitellusti. Suhteet, jotka kadulla elävät lapset ja nuoret luovat ympäristönsä kanssa, ovat seurausta jatkuvasta vuoropuhelusta henkilön omien halujen ja toiveiden sekä koettujen mahdollisuuksien välillä. Myös aikaisemmat kokemukset sekä tulevaisuuden toiveet vaikuttavat tähän vuoropuheluun.

Crianças e adolescentes perambulando pelas ruas, trabalhando, brincando, descansando nas sombras ou cometendo pequenos delitos. Esta cena cada vez mais é um elemento integral da dinâmica das cidades no mundo inteiro. Tais crianças são frequentemente mal‐entendidas, apesar das tentativas dos pesquisadores de reduzir a diferença entre a idéia geral a respeito das vidas nas ruas e das realidades experienciadas pelos moradores de ruas. Os estudos na área cobrem aspectos como modos de vida, motivos de estar nas ruas, métodos de sobrevivência, identidade e agência. Ao desconhecer ou ignorar esses aspectos, a sociedade comumente interpreta as crianças e adolescentes em situação de rua como as causas principais das problemas sociais como criminalidade, drogas e prostituição. Os elementos que formam as vidas nas ruas são indissociáveis, e devem ser considerados simultaneamente quando analisando as realidades nas ruas. Tais elementos são por exemplo elementos mentais e sociais, assim como suas interconexões com o ambiente físico nas cidades. É notável também que as ciências sociais não dedicam a atenção necessária aos aspectos como tristeza, angústia e baixa autoestima, ou a outros fatores mentalmente preocupantes nas ruas. Todos esses aspectos, humanos ou des‐humanos, têm significados distintos para cada indivíduo, e suas múltiplas interpretações também interagem com as circunstâncias individuais da vida na rua. Nesta tese de doutorado pesquiso as vidas das crianças e adolescentes em situação de rua na cidade de Pelotas, no sul do Brasil. A pesquisa utiliza uma metodologia tempo‐geográfica (time‐geography), que proporciona abordagens propícias à pesquisa das vidas destas crianças e adolescentes. Nesta tese eu respondo à três perguntas concretas: 1. Quais processos influenciam as redes multidimensionais às quais as crianças e adolescentes em situação de rua estão associados? 2. Como a relação entre estas crianças e adolescentes e o ambiente de rua é formado em relação ao tempo e ao espaço? 3. Quais são os processos por trás dos atos de crianças e adolescentes em situação de rua? Pesquisei 19 crianças e adolescentes e seus relacionamentos com ambientes multidimensionais utilizando vários métodos tradicionais como observação, entrevistas e conversas em grupos. Além disso, apliquei exercícios que planejei, tais como caminhadas, e também analisei poemas e canções escritas pelas crianças, assim como fotografias tiradas por eles. O foco de minha pesquisa são as interconexões entre dimensões do espaço mental, socio‐cultural e do ambiente físico das ruas. Ademais, ilustro como as próprias crianças e adolescentes em situação de rua são agentes ativos na definição de suas vidas nas ruas. Esta tese de doutorado demonstra que a vida na rua possui aspectos relativos, que se transformam constantemente por sucessivos encontros e secessões, que ao longo do tempo podem ser descritas como complexas redes. Também descrevo os vários processos associados à vida nas ruas, e como estes transformam as redes conectando‐as às múltiplos tempos e espaços. Analiso também como o legado histórico, do ponto de vista da legislação obsoleta, da reputação ou representação das crianças e adolescentes em situação de rua na mídia ou na literatura afetam fortemente as redes dessas crianças . Ainda que crianças e adolescentes tenham papel ativo na transformação das redes às quais eles estão associados, tais processos influem de maneira significativa em suas atividades. Certos aspectos do ambiente são abordados de maneira física, táctil, ou por meio da imaginação, de modo que as crianças possam atingir seus objetivos. Estas metas, por sua vez, são relacionadas, de uma maneira ou outra, com oportunidades que visem melhorar suas condições de vida, e de viver uma vida tão normal quanto possível. Para cumprir seus objetivos, estas crianças e adolescentes estabelecem distintas bolsões espaço‐temporais, sejam esses concretos, por meio de círculos sociais, ou simplesmente por meio da imaginação. As relações que as crianças e adolescentes em situação de rua desenvolvem com seus ambientes são produtos da negociação constante entre as ânsias e os desejos individuais e as oportunidades disponíveis ao indivíduo. Essa complexa negociação também é afetada por experiências do passado e a esperança em relação ao futuro.